Malaysia’s Financial Crisis And Contraction In Human Resource: Policies And Lessons For SMIs - Rujhan, Mustafa; Shazali, Abu Mansor (2005)
The economic crisis, which has recently occurred in Malaysia, has affected not only the economy in aggregate, but also to the labor market. The 6.7 per cent contraction of the economy in 1998 caused the employment growth to slacken and the unemployment rate to soar to 3.9 per cent. The 3.9 per cent unemployment rate was of great concern, as rising unemployment had implications on efforts to reduce poverty. The crisis has also resulted in the closure of some SMIs enterprises, particularly when tight monetary policies were implemented at the beginning of the crisis, causing disruption in operations and severe liquidity problems. The widespread of the crisis in Malaysia has triggered policy makers to immediately address the shortcomings pertaining to the labor market. The facilitating and regulatory role played by the Government in the labor market had eased tension among workers arising from the economic crisis. The harmonious industrial environment had in a way helped to expedite the economic recovery. The holistic approach by the government in addressing the labor issues incorporated both the demand and supply sides of the labor market. Accessibility of information is considered important, thus the government making it compulsory for employers to report any step taken that can give a signal to the labor market. In addition, policies designed during period of crisis involved the players in the market, the employers and employees. The holistic approach did not segregate policies according to sectors, ownership, gender or sizes of firms. Firms irrespective of the ownership functions and sizes are treated equally when addressing labor issues. Thus employees working in small and medium industries should not expect to receive better or lesser treatments when confronting economic crisis.